Electronic Participation 6th IFIP WG 8.5 International Conference, ePart 2014, Dublin, Ireland, September 2-3, 2014, Proceedings - Tambouris, Efthimios.; Tambouris, Efthimios.; Macintosh, Ann.; Macintosh, Ann.; Bannister, Frank Edward.; Bannister, Frank Edward. (Information Systems and Applications, incl. Internet/Web, and HCI, 2014)
This book constitutes the refereed proceedings of the 6th IFIP WG 8.5 International Conference on Electronic Participation, ePart 2014, held in Dublin, Ireland, in September 2014. The 11 revised full papers presented were carefully reviewed and selected from 20 submissions. The papers have been organized in the following topical sections: social media; review and analysis; engaging citizens online; and software platforms and evaluation.